Prioritization of Districts Based on Dairy Production - Bose, Jayavarathan; Murugan, Prabu; Amaresan, Serma S. P.; Kumaran, Sudeepkumar N.; Chirukandoth, Sreekumar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was carried out to prioritize the districts of Tamil Nadu state of India for identifying the dairy production potentials. Secondary  data on veterinary institutional facilities and livestock production were collected from an integrated sample survey report, Government  of Tamil Nadu, 2019-20. The data on rainfall, permanent pasture, gross cropped area, food grain production, cereal production,  rural agricultural labor, rural marginal workers, number of co-operative banks, number of rural cultivators, surface road length, and  landholding were based on Economic appraisal report, Government of Tamil Nadu, 2019-20. Factor analysis with principal component  extraction was applied to detect the interrelationship among attributes of dairy progressiveness. The study identified components such  as agriculture production, buffalo milk production, the component of veterinary infrastructure, and the component of cross-bred milk  production. Based on the calculated factor scores of each factor component, the relative position of each district in the state has arrived.  The districts of Namakkal, Salem, Thanjavur, Tiruvallur, and Cuddalore were ranked in top positions, and Dindigul, Ramanathapuram,  Theni, Thoothukudi, and the Nilgiris were ranked in bottom positions in dairy production. The study advocates proper planning and  prioritization of attributes among the districts to reduce variability for additional milk production.
Keywords: Dairy progressiveness; Factor analysis; Livestock production; Principal component approach; Regional disparity